2018
DOI: 10.18203/2320-1770.ijrcog20180879
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcome of unilateral versus bilateral laparoscopic ovarian drilling in clomiphene citrate resistant cases of polycystic ovarian syndrome: a comparative study

Abstract: Background: The aim of the current study is to compare the efficacy of laparoscopic unilateral ovarian drilling with bilateral ovarian drilling in clomiphene citrate resistant cases of polycystic ovarian syndrome in terms of clinical response, change in biochemical parameters, ovulation rate, pregnancy rate and miscarriage rate.Methods: The study was conducted on 45 women with anovulatory infertility due to PCOS with clomiphene citrate resistance. By random selection, all patients were divided in two groups. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Thereby, a suggested recommendation to apply a ULOD rather than a BLOD is generally in agreement with these data (Abu Hashim et al, 2018). Another agreement with our result by Laul et al, (2018) found that there was no statistically significant difference after unilateral and bilateral ovarian drilling in overall clinical response, ovulation rate, change in biochemical parameters, pregnancy rate and miscarriage rate. Youssef and Atallah, (2007) evaluated 87 patients with ovulation failure as a result of PCOS who were randomly allocated to unilateral ovarian drilling (N = 43) and bilateral ovarian drilling (N = 44).…”
Section: Unilateral Versus Bilateral Laparoscopic Ovarian Drilling In...supporting
confidence: 90%
See 3 more Smart Citations
“…Thereby, a suggested recommendation to apply a ULOD rather than a BLOD is generally in agreement with these data (Abu Hashim et al, 2018). Another agreement with our result by Laul et al, (2018) found that there was no statistically significant difference after unilateral and bilateral ovarian drilling in overall clinical response, ovulation rate, change in biochemical parameters, pregnancy rate and miscarriage rate. Youssef and Atallah, (2007) evaluated 87 patients with ovulation failure as a result of PCOS who were randomly allocated to unilateral ovarian drilling (N = 43) and bilateral ovarian drilling (N = 44).…”
Section: Unilateral Versus Bilateral Laparoscopic Ovarian Drilling In...supporting
confidence: 90%
“…The body mass index was 27.5 ± 2.4 for group I, and 28.7 ± 2.1 for group II (p < 0.23) (Kandil and Selim, 2005). Another study by Laul et al, (2018) found that the average age of patients in both the groups was found to be 27 years. The duration of marriage in both groups was same with a mean duration of infertility of 4 years.…”
Section: Unilateral Versus Bilateral Laparoscopic Ovarian Drilling In...mentioning
confidence: 88%
See 2 more Smart Citations
“…These results agree with Abdelhafeez et al [23] and Zahiri Sorouri et al [4] who reported a significant decrease in serum levels of LH and testosterone in women after LOD. Laul et al [24] reported that LOD has been associated with a significant decrease of basal serum LH levels. Basal LH reduction was already known to be an indicator of good response to LOD.…”
Section: Discussionmentioning
confidence: 99%